Educational differences in mortality but not in risk of recurrence following first-time pulmonary embolism: A Danish nationwide register-based study. Issue 219 (November 2022) - Sonne-Holm, Emilie; Kjærgaard, Jesper; Bang, Lia E.; Køber, Lars; Fosbøl, Emil; Carlsen, Jørn; Winther-Jensen, Matilde
Abstract: Background: Several studies agree that high socioeconomic position is protective against risk of PE. However, socioeconomic impact on outcomes from PE is not known. In this paper we aimed to compare differences in risk of recurrence and mortality within the first year following a first-time PE across level of education. Methods: Using Danish national registers, patients ≥18 years of age hospitalized with a first-time PE between 1998 and 2018 were registered. Based on International Standard Classification of Education system 2011 patients were divided into four levels of education. Risk of recurrence and death across educational level were assessed by cumulative incidence curves and multivariable adjusted absolute risk regression analyses. Results: In total, 22, 708 patients with basic education (60 % women, median age 73 years), 19, 809 with high school/vocational education (43 % women, median age 67 years), 7257 with short/medium higher education (54 % women, median age 65 years) and 2410 with long higher education (34 % women, median age 64 years) were hospitalized for PE. Risk of recurrence was not influenced by increasing educational level (relative absolute risk (RAR) 0.97, [95 % confidence interval (CI), 0.85–1.11], RAR 1.01 [95 % CI, 0.85–1.19], RAR 0.81 [95 % CI, 0.60–1.09]) compared to basic education, however, risk of death decreased with increasing level of education (RAR 0.93 [95 % CI, 0.90–0.96], RAR 0.88 [95 % CI, 0.83–0.92], RAR 0.83 [95 % CI, 0.76–0.89]). Conclusion: Significant educational differences exist in mortality following PE, warranting a need for socially differentiated efforts targeted towards patients with low educational status.